Regulation of plasma membrane calcium ATPase (PMCA) by actin cytoskeleton - Vigil, Maximiliano Angel (2021)
The Plasma Membrane Calcium ATPase (PMCA) is a calmodulin-modulated P-type ATPaseresponsible for the maintenance of low intracellular concentrations of Ca2+ in mosteukaryotic cells. Our group have previously shown that purified actin can exert a dualmodulation on the activity of Ca2+-ATPase 4b isoform (hPMCA4b): F-actin inhibits it whileshort actin oligomers may contribute to its activation. These studies had to be performedwith purified proteins given the nature of the biophysical and biochemical approachesused.On the other hand, in HEK293 human cells that overexpressed PMCA2w/b isoform, theactin depolymerization upon Cytochalasin D (CytD) treatment significantly increasedPMCA2-mediated Ca2+ extrusion and when F-actin was stabilized using jasplakinolide,PMCA2w/b activity was completely abolished.In order to assess whether the functional interaction between the hPMCA4 isoform and theactin cytoskeleton may be of physiological relevance, we decided to further characterize itin the context of a living cell by monitoring in real-time the changes in the actinpolymerization and cytosolic Ca2+ concentration ([Ca2+]cyt). For this, hPMCA4 isoform wastransiently expressed in HEK293T cells. The dynamics of [Ca2+]cyt was performed usingthe fluorescent probe Fluo-4 and studying the alterations in [Ca2+]cyt generated by Ca2+release from the endoplasmic reticulum, and by extracellular Ca2+ entry through store-operated Ca2+ channels. The dynamics of actin polymerization was performed transientlyexpressing LifeAct-Ruby.Results show that the alteration of actin polymerization by CytD treatment significantlyincreased hPMCA4 activity (102%). On the other hand, in absent of CytD, actinpolymerization dynamics did not change after TG stimulus, while after Ca2+ stimulus, anactin reorganization was observed. This reorganization takes place at the same times thatthe hPMCA4 increases its activity, suggesting that hPMCA4 may be activated by actindepolymerization in the cells.